The Effect Zeolite Addition in Natural Rubber Polypropylene Composite on Mechanical, Structure, and Thermal Characteristics - Bukit, Nurdin; Frida, Erna (Makara Journal of Technology, 2013)
This study was conducted to determine the effect of zeolite as filler on mechanical properties, and thermal structure blends of natural rubber and polypropylene (NR/PP). In this study, NR/PP/PP-g-MA blends was filled uncalcined zeolite and calcined zeolite at different weight percent of the 2, 4, and 6%. Samples were characterized to determine the tensile strength, fracture elongation and Young's modulus. Structure of the samples was investigated using XRD method and thermal characteristics were analyzed using DTA/TGA technique. The results obtained for tensile strength showed a significant influence with the addition zeolite of the NR/PP blends at 2% by weight of the composition (8 MPa) and decreased with increasing zeolite composition uncalcined zeolite or calcined zeolite. At 2% to 6% by weight of an increase in Young's modulus, for which uncalcined zeolite function more effectively than the calcined zeolite. On the other hand, the addition of uncalcined zeolite and calcined zeolite did not result in decreased fracture elongation. The XRD analysis zeolite indicate the existence of amorphous phase and crystalline mineral type mordenite (CaAl2Si10O24.7 H2O). In general, cristality of samples filled with calcined zeolite slightly higher than the uncalcined zeolite at the same amount and intercalation occurs between the zeolite matrix NR/PP. Thermal analysis showed that the samples are filled with calcined zeolite has a thermal resistance higher than the uncalcined zeolite, the melting point NR/PP 165.0 °C with the addition of 6 wt% zeolite melting point to 186.7 °C.